Pengaruh Kadar Air terhadap Nilai Kuat Geser Batulempung pada Cekungan Kutai Menggunakan Metode Direct Shear di Provinsi Kalimantan Timur - Muhammad Rahul Shidiq; Tommy Trides; Albertus Juvensius Pontus; Revia Oktaviani; Ardhan Ismail; Rety Winonazada (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
In the Kutai Basin area, seasonal changes such as high rainfall can significantly increase groundwater content, so that the effect of water content on the shear strength of claystone, increasing water content in rocks tends to decrease shear strength. Water in the pores or fractures can increase pore water pressure and reduce effective normal stress. Shear strength is one of the most important mechanical parameters used to assess soil and rock stability, this parameter is very important in slope stability analysis, foundation planning, and various civil engineering and mining applications. Therefore, this study was conducted to determine whether the water content in rocks can affect the strength of rocks in receiving shear forces. The method used in this study is more quantitative and specific to the effect of water content on the shear strength of claystone in this area. Increasing water content in rocks tends to reduce shear strength. This study was conducted by taking claystone samples from several locations in the Kutai Basin. Data collection in the form of primary data and secondary data for testing physical properties and testing mechanical properties, in testing physical properties, the water content value will be taken as supporting data which is one of the factors that affect rock strength, in testing mechanical properties, claystone shear strength data will be taken. From the results of the physical properties test calculations, the air content in each Formation is obtained, namely, in the Kampungbaru Formation the minimum air content value is 15.54% and the maximum is 20.17%, in the Balikpapan Formation the minimum air content value is 10.21% and the maximum is 12,88%, in the Palaubalang Formation the minimum air content value is 10.49% and the maximum is 22.87%. The results of the strength of the claystone in receiving shear forces in the Kutai Basin are the Muara Jawa location 0.486MPa, Tanah Datar location 0.500 MPa, Sanga-sanga location 0.333 MPa, Muara Badak location 0.269, Air Putih location 0.711MPa, Mugirejo location 0.021 MPa and Lempake location 0.092 MPa.